2011
DOI: 10.1590/s0085-56262011000100021
|View full text |Cite
|
Sign up to set email alerts
|

Host preference of the egg parasitoids Telenomus remus and Trichogramma pretiosum in laboratory

Abstract: Host preference of the egg parasitoids Telenomus remus and Trichogramma pretiosum in laboratory. This research aimed to evaluate the host preference of the egg parasitoids Telenomus remus and Trichogramma pretiosum. Trials were carried out in laboratory, under controlled environmental conditions (25 ± 2ºC temperature; 70 ± 10% RH; and 14 h photophase). The parasitoid searching behavior was evaluated based on the distribution (%) of eggs parasitized by each parasitoid, on egg masses of each host species. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 15 publications
3
16
1
2
Order By: Relevance
“…These conclusions differ from Goulart et al (2011) who had previously reported non-preference of T. remus for S. frugiperda eggs after the parasitoid be reared on those eggs for several generations. Accordingly to these authors it would demonstrate that the host acceptance or preference behavior of the T. remus females could not be attributed to the pre-imaginal conditioning described by Cobert (1985) and Kaiser et al (1989).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These conclusions differ from Goulart et al (2011) who had previously reported non-preference of T. remus for S. frugiperda eggs after the parasitoid be reared on those eggs for several generations. Accordingly to these authors it would demonstrate that the host acceptance or preference behavior of the T. remus females could not be attributed to the pre-imaginal conditioning described by Cobert (1985) and Kaiser et al (1989).…”
Section: Discussioncontrasting
confidence: 99%
“…Accordingly to these authors it would demonstrate that the host acceptance or preference behavior of the T. remus females could not be attributed to the pre-imaginal conditioning described by Cobert (1985) and Kaiser et al (1989). However, it is important to point out that Goulart et al (2011) compared T. remus preference among Spodoptera spp. eggs.…”
Section: Discussionmentioning
confidence: 97%
“…The number of A. gemmatalis eggs parasitized by T. remus when the parental female was reared on the same species was lower than the number of parasitized eggs of its natural host S. frugiperda at all temperatures. These results support the assumption of co-evolution of those species (Goulart et al 2011). Even when parasitoids were reared on the alternative host (A. gemmatalis) for one generation, parasitism was still higher on eggs of its natural host (S. frugiperda) on which the parasitoid was reared in the laboratory for years.…”
Section: Discussionsupporting
confidence: 80%
“…Despite that, Brazilian researchers have reported exclusively the individually-cultured larvae when rearing FAW, always justifying it with the occurrence of larval cannibalism (e.g. Goulart et al 2011;Vilarinho et al 2011;Bueno et al 2010Bueno et al , 2008.…”
Section: Resultsmentioning
confidence: 99%